3: How to check the level of water in the cooling tank on your diesel-powered maize shelling machine - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
How to check the water level before starting the engine for the first time every day. Water Gauge Up indicates water tank is full; Water Gauge Down indicates water tank is empty. Low water level can result in overheating the engine or cause the engine to cease if not checked. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.